PENGARUH PENGGUNAAN LABA DAN ARUS KAS TERHADAP PERMASALAHAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR - Sulbahri, Rifani Akbar; Febriyanti, Melda Febriyanti (Balance : Jurnal Akuntansi dan Bisnis, 2019)
This study aims to determine the effect of the use of earnings and cash flow on financial distress in manufacturing companies (metal industry sub-sector and the like in the Indonesia Stock Exchange in 2014-2018). This research on financial distress uses a quantitative approach. The study population includes all metal manufacturing sub-sector manufacturing companies and the like on the Indonesia Stock Exchange in 2014-2018. The sample in this study were 7 companies that were determined by purposive sampling technique. The data analysis method used is multiple linear regression analysis. The results showed that (1) Profit had a positive effect on financial distress. This is indicated by a regression coefficient of 0.038 and a calculated t value of 1.675. t count < t table that is 1.675 < 1.69389. The value of t arithmetic shows that earnings have a positive effect on financial distress. With a significance level of less than 5% (0.004 < 0.05). (2) Cash flow does not affect financial distress. This is indicated by a regression coefficient of 0,000 and a calculated value of -0,060. t arithmetic < t table that is -0.060 < 1.69389, the value of t arithmetic shows that cash flow has no positive effect on financial distress. With a significance level of more than 5% (0.952 > 0.05). (3) The determination determination R2 of 0.292 (29.2%) illustrates that the effect of earnings and cash flow on financial distress is 29.2% while the remaining 70.8% is influenced by other factors.